Perspective 82. - Art Basel Basel 1982 (Basel : Art Internationale Kunstmesse Basel, 1982)
Bauch, Michael ; Blanchard, Rémy ; Blum, Jörg ; Buchli, Rudolf ; Cantalup, M. Patrizia ; Cohen-Or, Beni ; Combas, Robert ; Fortuna, Pietro ; Frank, Dale ; Gabriel, Paula ; etc.
Perspective 82, Art 13'82, Basel, 16. - 21. Juni 1982
boek